Características físicas, estruturais e mecânicas de instrumentos endodônticos de NiTi ProTaper - Renata de Castro Martins (2008)
A study on the structural, physical and mechanical characteristics of ProTaper nickeltitanium endodontic instruments was performed in this work. The geometric and dimensional aspects of the instruments were analyzed by optical microscopy. Simulated resin curved canals prepared with the instruments were evaluated using an image analysis software in order to verify canal geometry. Surface topography of the instruments was observed by scanning electron microscopy (SEM), their chemicalcomposition was analyzed semi-quantitatively by X-ray energy dispersive spectroscopy (EDS), and the phases present in the alloy were identified by X-ray diffraction (XRD). The transformation temperatures of the material were determined by differential scanning calorimetry (DSC). The mechanical behaviour of the instruments was evaluated by means of torsion and bending tests, performed according to ISO 3630-1specifications. Fatigue resistance was evaluated using a bench test device employing an artificial canal with a 5mm curvature radius and angle of curvature of 45°. The influence of cyclic straining in torsion on torsional properties and on fatigue resistance of the instruments was also evaluated. The instruments presented good geometricstandardization, acceptable surface properties, adequate equiatomic ratio, predominance of the phase, and transformation temperatures favoring superelasticity. There was a good agreement between the diameters of the simulated resin curved canals prepared with the instruments and the dimensions of the last instruments used to shape them. All instruments worked at the tip and along their cutting blades. The maximum torque and the bending moment at 45° were higher for instruments with larger diameter and cross sectional area at 3mm from the tip. The instruments previously cycled in torsion showed a lower maximum torque when compared with new instruments. With the exception of S1 instruments, there was a tendency of decreasing NCF after torsional cycling. Only F1 and F2 instruments followed the Coffin-Manson´s relation, stating that the number of cycles to failure varies inversely with the strain amplitude. The S1and S2 instruments can fail by two distinct mechanisms: fatigue in the apical portion and overloading in torsion in the coronal and middle thirds. The F1 and F2 instruments can fail, in the apical portion, by torsional